The Normative Framework of Family Finance in Islam: Between Religious Doctrine and Contemporary Social-Economic Discourse - Nizami, Auliya Ghazna (Maliyah : Jurnal Hukum Bisnis Islam, 2025)
Abstract: This article explores the normative foundations of family finance in Islam by examining key doctrines within classical and contemporary fiqh literature. The study focuses on fundamental aspects such as financial responsibilities (nafaqah), wealth management, and intra-household economic roles. It adopts a doctrinal approach to analyze legal texts from major Islamic legal schools (madhāhib), while engaging critically with selected modern social and economic theories to enrich the normative discussion. By juxtaposing Islamic jurisprudential insights with contemporary discourses on household economics, gender roles, and financial planning, the article seeks to offer a balanced and context-aware understanding of Islamic family economy. This synthesis aims to highlight both the enduring relevance and adaptive potential of Islamic legal principles in addressing the economic realities faced by Muslim families today. Keywords: Family Finance; Fiqh; Contemporary Social-Economy Discourse.   Abstrak: Artikel ini mengeksplorasi fondasi normatif keuangan keluarga dalam Islam dengan memeriksa doktrin kunci dalam literatur fiqh klasik dan kontemporer. Studi ini berfokus pada aspek mendasar seperti nafkah wajib (nafaqah), manajemen kekayaan, dan peran ekonomi intra-rumah tangga. Ini mengadopsi pendekatan doktrin untuk menganalisis teks-teks hukum dari aliran hukum Islam utama (madhāhib), sambil terlibat secara kritis dengan teori-teori sosial dan ekonomi modern yang dipilih untuk memperkaya diskusi normatif. Dengan menyandingkan wawasan yurisprudensi Islam dengan wacana kontemporer tentang ekonomi rumah tangga, peran gender, dan perencanaan keuangan, artikel ini berusaha menawarkan pemahaman yang seimbang dan sadar konteks tentang ekonomi keluarga Islam. Sintesis ini bertujuan untuk menyoroti relevansi abadi dan potensi adaptif prinsip-prinsip hukum Islam dalam mengatasi realitas ekonomi yang dihadapi oleh keluarga Muslim saat ini. Kata kunci: Keuangan Keluarga; Fiqh; Wacana Sosial-Ekonomi Kontemporer.